The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.17744/mehc.39.3.04
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Mental Health Literacy of Clergy: An Informational Resource for Counselors

Abstract: Though clergy often serve as informal helpers and conduits to the formal mental health care system, few researchers have examined whether such clergy maintain the knowledge necessary to complete this mission. In this study, denominational affiliation, educational variables, and demographic characteristics were examined as potential predictors of mental health literacy (MHL). As a measure of MHL, the Mental Health Literacy Scale was completed by a nationwide sample of 238 Christian clergy. The results provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 36 publications
6
20
2
Order By: Relevance
“…Few studies have addressed demographic differences in MHL, including those along racial/ ethnic or gender lines. In one study, Vermaas et al (2017) found no differences in mental health literacy rates among clergy of various denominations, including historically Black protestant groups. Some research (Hee Yun Lee et al, 2020;Leighton, 2010) found evidence that there are gender differences in MHL, with women having more social support for and awareness of mental health disorders than do men.…”
Section: Introductionmentioning
confidence: 97%
“…Few studies have addressed demographic differences in MHL, including those along racial/ ethnic or gender lines. In one study, Vermaas et al (2017) found no differences in mental health literacy rates among clergy of various denominations, including historically Black protestant groups. Some research (Hee Yun Lee et al, 2020;Leighton, 2010) found evidence that there are gender differences in MHL, with women having more social support for and awareness of mental health disorders than do men.…”
Section: Introductionmentioning
confidence: 97%
“…As one might expect, these results are below that of mental health professionals [M = 145.5, SD = 7.2, N = 43; ( 31 )], t (106) = 10.33, p < 0.0001. They were also found to be lower than members of the clergy [M = 134.2, SD = 10.8, N = 238; ( 38 )], t (414) = 3.18, p = 0.002 who presumably have some experience of working with individuals with mental health concerns. Frontline pediatric staff's MHLS scores were found to be higher than a community sample [M = 127.38, SD = 12.63, N = 372; ( 31 )], t (413) = 3.18, p = 0.001 and UK medical students [M = 127.56, SD = 11.8, N = 25; ( 11 )], t (417) = 2.88, p = 0.004 who may not have had any prior exposure to working with mental health concerns.…”
Section: Resultsmentioning
confidence: 97%
“…However, the number of participants relatively low as compared to the current study. Vermaas, Green, Haley and Haddock (2017) administered the similar MHL scale to 238 clergy of different denominations across the United States. This study aims to compare the different of MHL score among different study groups consisting of evangelical Protestant (n=118), mainline Protestant (n=78), Catholic (n=39), historically Black Protestant (n=3) participants.…”
Section: Discussionmentioning
confidence: 99%